Pengembangan Sistem Pengolahan Air Siap Minum di Daerah Bencana dengan Water Purifier, Solar Cell, dan IoT - Tarmin Abdulghani; Trini Handayani; Siti Nazilah; Fietri Setiawati Sulaeman; Didik Notosudjono; Sata Yoshida Srie Rahayu; Yuli Wahyuni; Layung Paramesti Martha (Warta LPM, 2024)
The Kosabangsa program is a community building activity with collaboration between universities funded by the Directorate of Research, Technology, and Community Service located in Cijedil Village, Cianjur Regency. After the earthquake in November 2022 impacted Cijedil Villagers who lacked clean water due to damage to the water infrastructure. In Kosabangsa 2023, activities carried out in Cijedil Village aim to strive to increase the availability of clean water through the implementation of innovative technology in processing ready-to-drink water by utilizing a Water Purifier with additional technology in the form of Solar Cell energy and IoT. This research focuses on efforts to increase the access of the Cijedil Village community to safe and quality water. This research methodology includes an initial survey to evaluate the water conditions in Cijedil Village and the design and development of a water purifier system with the addition of solar cells and IoT technology. Kosabangsa's activities involve active community participation to ensure sustainability at the community level. The results showed that the application of a Water Purifier for water treatment, Solar Cell for power generation, and IoT technology for monitoring the function of water treatment devices was able to increase the amount and quality of drinking water availability in Cijedil Village from 10,000 liters per day to 30,000 liters per day. This technology positively impacts the availability of ready-to-drink water and public health. This research is expected to guide and inspire the development of similar solutions in other places and ensure water availability during emergencies after disasters.